Tabuh Leluangan in the Piodalan Ceremony in Banjar Buagan, Pemecutan Kelod, Denpasar, Bali - I Kadek Agus Erwan Maherwan (Institut Seni Indonesia Bali, 2026)
The development of the times has driven many changes in the community environment, including in the Balinese Karawitan community. One significant change is the rise of gending from Seka Gong Buagan, Pemecutan Kelod, Denpasar, Bali, namely gending leluangan, which origins and the form of the gending itself are unknown. Unwittingly, these tabuh tabuh have undergone changes in style over time by different trainers so that they can be debated by the penglingsir and Pemangku in the Dewa Yadnya ceremony. This study aims to investigate the origin of gending leluangan in Dewa Yadnya as well as its form and instrumentation. The research method used is a survey and statistical data analysis, with penglingsir who are still actively involved in Seka Gong Buagan. The results show that the gending used in the Dewa Yadnya Ceremony in Banjar Buagan is a leluangan type of gending that has experienced changes in rhythm, tempo, dynamics and harmony or different gangsa strokes so that problems arise in its structure. This finding indicates that the gending leluangan has the same structure as leluangan in general but has its own unique melody so that the percussion is not widely known by the local community and is only used in the Dewa Yadnya ceremony in Banjar Buagan.